Impact of covid-19 pandemic on the epidemiology and etiology of lower respiratory tract infections in children : Vpliv pandemije Covid-19 na epidemiologijo in etiologijo okužb spodnjih dihal pri otrocih - Berce, Vojko; Časl, Leon (Acta Medico-Biotechnica, 2023)
Purpose: Changes in the epidemiology of communicable diseases in children are one of the direct and measurable consequences of the coronavirus disease 2019 (COVID-19) pandemic. Therefore, this study aimed to evaluate the impact of the recent pandemic on the epidemiology of lower respiratory tract infections and the relevant causative pathogens other than severe acute respiratory syndrome coronavirus 2. Methods: In this retrospective study, all children hospitalized due to lower respiratory tract infections in 2019 and 2021 were enrolled. The nasopharyngeal swab test was performed using polymerase chain reaction to identify prevalent respiratory viruses and atypical bacteria. Results: A total of 356 children were hospitalized due to lower respiratory tract infections in 2019 and 250 children in 2021 (a reduction of 29.8%). The proportion of children hospitalized due to atypical pneumonia and bacterial pneumonia decreased from 10.1% and 21.9% in 2019 to 2.8% and 12.0% in 2021, respectively (P
Keywords: children, COVID-19, epidemiology, etiology, lower respiratory tract infections, severe acute respiratory syndrome coronavirus 2